I am cute dresses 25 simple designs to sew - Watanabe, Sato; Ohashi, Asako (Loveland, CO Interweave Press LLC, 2011)
"Including tunics, halters, sundresses, and more, these ... dresses are created from basic, one-size-fits-many shapes and designed to be flattering on everyone"--P. [4] of cover.
Chapter headings: I am pleats & petals -- I am very V-neck -- I am Mandarin empire -- I am barely ruffled -- I am peekaboo sleeves -- I am hello halter -- I am simply stand-up -- I am baby bateau -- I am sassy sundress -- I am twice as nice -- I am tiny tucks -- I am raglan to riches -- I am all the trimmings -- I am all wrapped up -- I am dainty drops -- I am cute contrast -- I am sweetly tied -- I am triple tier -- I am jumper for joy -- I am sew buttoned down -- I am shift into tunic -- I am magical insets -- I am kimono cut -- I am box-pleated wonder -- I am satin doll -- Construction tips -- Basic techniques -- Glossary -- Fabric layouts and instructions.
Translation of: Chokusen-nui de suteki na one piece.
"Originally published in Japanese language by Kawade Shobo Shinsha Publishers"--T.p. verso.
In English, translated from the Japanese.
Keywords: Dressmaking; Dresses; Sewing